THE MESSAGE OF CORPORATE GOVERNANCE TO SHAREHOLDERS IN ENHANCING FIRM FINANCIAL PERFORMANCE - Hossian, Ibrahum Ali (Transpublika Publisher, 2024)
The current study highlighted the importance of corporate governance in improving a company's financial performance and increasing shareholder value. Shareholders buying shares show their trust in a company's management and future outlook, emphasizing the significant impact of corporate governance structures. This study examines how corporate governance mechanisms address shareholder concerns and impact a company's financial success by aligning company goals with shareholder interests. It aims to determine how corporate governance mechanisms can be adjusted to ensure shareholders are properly rewarded while also protecting the company's long-term objectives. The study addresses both the theoretical and practical aspects of corporate governance mechanisms, assessing their impact on shareholder value through transparent communication and accountability. It stresses the importance of clearly defining company goals and strategic plans to establish a solid governance framework that can meet shareholder expectations. The study compares the broader role of corporate governance with a detailed analysis of principles that prioritize shareholder interests and needs. This study tries to underline the efficacy of corporate governance tools at leveraging financial performance and guaranteeing value for stockholders. These conceptual frameworks and practical evidence go a long way in giving insight into how corporate governance tools are supposed to make a difference toward success.